2022
DOI: 10.1002/elsc.202100157
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the growth kinetics and stoichiometry of Escherichia coli at the single‐cell level

Abstract: Microfluidic cultivation and single-cell analysis are inherent parts of modern microbial biotechnology and microbiology. However, implementing biochemical engineering principles based on the kinetics and stoichiometry of growth in microscopic spaces remained unattained. We here present a novel integrated framework that utilizes distinct microfluidic cultivation technologies and single-cell analytics to make the fundamental math of process-oriented biochemical engineering applicable at the single-cell level. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 63 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…A K S of approx. 0.5 mg L −1 has been reported for wild‐type E. coli MG1655 (Smaluch et al, 2023), while the estimated K S of strain WGM is 10 mg L −1 (Krausch et al, 2023). This 20‐fold decreased affinity may result in a growth rate controlled by the glucose concentration at the end of the culture, which can be detected due to the relatively high cell density.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…A K S of approx. 0.5 mg L −1 has been reported for wild‐type E. coli MG1655 (Smaluch et al, 2023), while the estimated K S of strain WGM is 10 mg L −1 (Krausch et al, 2023). This 20‐fold decreased affinity may result in a growth rate controlled by the glucose concentration at the end of the culture, which can be detected due to the relatively high cell density.…”
Section: Resultsmentioning
confidence: 94%
“…It was shown that the cAMP‐Crp complex pool is a function of the glucose uptake rate (You et al, 2013) and probably sensitive to the carbon uptake rate (Okano et al, 2020). The affinity for glucose is heterogeneous in cultures of E. coli (Smaluch et al, 2023), and thus q gluc can also vary from cell‐to cell. Overall fitness is also heterogeneous in bacterial cultures (Henrion et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific growth rate values for the SGR control system were obtained in conjunction with the evaluation of the biomass concentration. The following equation was used to calculate the SGR for the time interval [42] : where μ is the specific growth rate.…”
Section: Methodsmentioning
confidence: 99%
“…The values proposed in Table 3 , as well as the initial values ( =0.5 g kg −1 , =5 g kg −1 , =8 kg), were taken from the research works of [17] , [28] , [42] . The controller parameter was manually recalibrated in the cultivation process data of the BL21 (DE3) pET21-IFN-alfa-5 strain.…”
Section: Investigation Of the Sgr Control System Performancementioning
confidence: 99%